IMPROVING READING COMPREHENSION SKILL OF THE SEVENTH GRADE STUDENTS’ AT MTS MUHAMMADIYAH PADANGPANJANG BY USING VISUALIZATION STRATEGY - Sri Ariani, Rini Hendrita Hafiza Aini (FKIP UMSB, 2023)
Thisresearch aimsatexaminingthe effectiveness of using visualization strategyas a medium in teaching reading comprehension. Meanwhile, the purpose of thisresearch is to knowif there is an effect ofof visualization strategytowardstudents’ reading comprehension skill. The modelof this research was pre-experimental research in a design group which is divided into three stages: pre-test, treatment, and post-test in learning process. The sample of this research wasVII Tahfidz grade at MTs Muhammadiyah Padangpanjang. Istruments tocollectthe data were pre-test and post-test through students’ performence with a writtentest and measured using an assessment rubric. Furthermore, the criteria forsuccsessweredeterminedonsixindicators:mainidea,fact,reference,vocabulary, inference, and purpose. As a quantitative research, the researcheranalyzed the data by using the T-test. The result showed that there was asignificant effect of students score by using visualization strategy in the readingcomprehensionoflearning process. The total score of the students in the pre-testwas 875 and the mean was 48,61. Then, the total score of the students in the post-test was 1.525 and the mean was 84,72.Then,Tcountishigher than Ttable (-13,5405 -1,69092). It means there is an improvement in visualization strategytoward reading comprehension in descriptive text. So, the visualization strategyforteachingreadingtoVIITahfidzstudentsofMTsMuhammadiyahPadangpanjang was effective.